Access control model to the systems containing the interchangeable objects - Sergey Aleksandrovich Lapin (Безопасность информационных технологий, 2016)
This article describes the access control model which extends TBAC. The model is applied in the systems containing the interchangeable objects. Model elements and properties, are defined formally